Environmental peacebuilding as a pathway to peace with nature - Sylvester, Janelle; Castro Nunez, Augusto (2024)
Environmental peacebuilding offers a pathway to address the complex interplay between conflict, environmental degradation, and governance by fostering sustainable natural resource management and community resilience. In regions heavily dependent on ecosystems for livelihoods, such as post-conflict Colombia, poor governance and non-participatory conservation efforts can exacerbate tensions and lead to renewed conflicts over resources. By integrating conflict-sensitive conservation strategies with inclusive governance, environmental peacebuilding promotes sustainable livelihoods and biodiversity conservation, advancing goals like the Global Biodiversity Framework and the Sustainable Development Goals. Strengthening governance, fostering equitable resource management, and securing sustainable financing are crucial steps toward achieving lasting "Peace with Nature" and ensuring both human and environmental well-being.